Prognostic factors in conversion surgery following nab‐paclitaxel with gemcitabine and subsequent chemoradiotherapy for unresectable locally advanced pancreatic cancer: Results of a dual‐center study. Issue 1 (16th August 2022) - Igarashi, Takamichi; Yamada, Suguru; Hoshino, Yui; Murotani, Kenta; Baba, Hayato; Takami, Hideki; Yoshioka, Isaku; Shibuya, Kazuto; Kodera, Yasuhiro; Fujii, Tsutomu
Abstract: Background: In pancreatic ductal adenocarcinoma (PDAC), only radical surgery improves long‐term survival. We focused on surgical outcome after induction gemcitabine along with nab‐paclitaxel (GnP) and subsequent chemoradiotherapy (CRT) with S‐1 administration for unresectable locally advanced (UR‐LA) PDAC. Methods: We retrospectively analyzed 144 patients with UR‐LA PDAC between 2014 and 2020. The first‐line regimen of induction chemotherapy was GnP for 125 of the 144 patients. Of the 125 patients who received GnP, 41 who underwent radical resection after additional preoperative CRT were enrolled. We evaluated the prognostic factors for this treatment strategy. Results: The median length of preoperative GnP was 8.8 months, and 30 (73%) patients had normalized CA19‐9 levels. R0 resection was achieved in 36 (88%) patients. Postoperative major complications of ≥Clavien–Dindo grade IIIa developed in 16 (39%) patients. With a median follow‐up of 35.2 months, 14 (34%) patients developed distant metastasis postoperatively. Using the Kaplan–Meier method, prognostic analysis of the 41 cases revealed the 3‐y overall survival rate (OS) was 77.4% and the 5‐y OS was 58.6%. In univariate analysis, length of preoperative GnP (≥8 months), CA19‐9 normalization, and good nutritional status at operation (prognostic nutritional index ≥41.7) were significantly associated with favorable prognosis. Multivariate analysis revealed CA19‐9 normalization (hazard ratio [HR] 0.23; P  = .032) and prognostic nutritional index ≥41.7 (HR 0.05; P  = .021) were independent prognostic factors. Conclusion: For surgical outcome after induction GnP and subsequent CRT for UR‐LA PDAC, CA19‐9 normalization and maintenance of good nutritional status during treatment until surgery were important for prolonged prognosis. Abstract : For radical surgery after induction gemcitabine along with nab‐paclitaxel and subsequent chemoradiotherapy for unresectable locally advanced pancreatic ductal adenocarcinoma, CA19‐9 normalization and maintenance of good nutritional status during treatment until surgery were important for prolonged prognosis.